PIV and WPIV: Two New Performance Indices for Heterogeneous Systems Evaluation - Branco, Kalinka R. L. J. Castelo; Santana, Marcos José; Santana, Regina H. C.; Bruschi, Sarita Mazzini; Kawabata, Célia leiko Ogawa; Ordonez, Edward David Moreno (INFOCOMP Journal of Computer Science, 2006)
Two new performance indices (PIV - Performance Index Vector and WPIV – Weighted Performance Index Vector) are presented in this article. Those indices to evaluate heterogeneous computing systems are based on a Euclidian metric. Aiming to maximize the use of the machines, the proposed indices are a combination of several usual indices and the results of their evaluation through a simulator show an appropriate behavior for different kinds of applications.